2015
DOI: 10.1039/c5cs00339c
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic chemistry with nitrous oxide

Abstract: This review article summarizes efforts to use nitrous oxide (N2O, 'laughing gas') as a reagent in synthetic chemistry. The focus will be on reactions which are carried out in homogeneous solution under (relatively) mild conditions. First, the utilization of N2O as an oxidant is discussed. Due to the low intrinsic reactivity of N2O, selective oxidation reactions of highly reactive compounds are possible. Furthermore, it is shown that transition metal complexes can be used to catalyze oxidation reactions, in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
118
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 197 publications
(157 reference statements)
2
118
0
4
Order By: Relevance
“…Ther egioselectivity of the products,w ith the triazene functional group next to the ester groups,w as confirmed by single-crystal X-ray analysis of ac rystal of 18 (for details see the Supporting Information). These results demonstrate that 1-alkynyltriazenes are compatible with as trong Lewis acid such as Sc(OTf) 3 .…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Ther egioselectivity of the products,w ith the triazene functional group next to the ester groups,w as confirmed by single-crystal X-ray analysis of ac rystal of 18 (for details see the Supporting Information). These results demonstrate that 1-alkynyltriazenes are compatible with as trong Lewis acid such as Sc(OTf) 3 .…”
mentioning
confidence: 60%
“…Research in our laboratory is directed towards the development of useful synthetic procedures involving nitrous oxide (N 2 O, "laughing gas"). [3] Recently,w eh ave discovered that it is possible to prepare 1-alkynyltriazenes by reaction of lithium amides with nitrous oxide and alkynyl Grignard reagents. [4] This simple method allows access to av ariety of 1-alkynyltriazenes in good yields.W hile aromatic triazenes have been studied extensively in the context of synthetic organic [5] and medicinal chemistry, [6] thec hemistry of 1-alkynyltriazenes is completely unexplored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43][44][45] Molecular sterics tructure has received much attentioni n synthetic chemistry,b ut ignored in the field of supramolecular self-assembly,asi tonly can be clearly understood through theoretical calculations. [46][47][48][49] Because noncovalent interactions are the main force for supramolecular self-assembly,a ny tiny change in the molecular structure would affect the noncovalent interactions and further change the self-assembly process. When C, N, or Oa toms act as linkersi namolecule, they are often in as p 3 -hybridized state.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our investigations about the chemistry of N 2 O, we recently observed that mesoionic and carbanionic N‐heterocyclic carbenes were able to capture N 2 O to give stable covalent adducts . These results prompted us to question whether the new N 2 O adducts could also be used to prepare azo dyes.…”
Section: Introductionmentioning
confidence: 99%